2013
DOI: 10.1177/0193945912473370
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Diabetes Self-Management Among African American Adults

Abstract: The rising incidence of diabetes complications among African Americans is a major health concern. Few studies have addressed gender differences in diabetes self-management in this population. The purpose of this study was to determine whether gender differences in facilitators and barriers to self-management exist among African American adults with type 2 diabetes. Thirty-eight participants were recruited from community agencies and each participated in one of seven audio-recorded focus group sessions. Regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 21 publications
1
43
1
Order By: Relevance
“…al (2013) found that African American men with type 2 diabetes cited lack of time at work, lack of family support, and lack of knowledge as the most frequent barriers to achieving self-management. 18 While men in our study also identified the latter two as challenges, lack of time at work was not discussed as a barrier; in this sample nearly all of the participants were unemployed. The importance of convenience and ease of access emerged as key factors for participation in a community-based intervention.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…al (2013) found that African American men with type 2 diabetes cited lack of time at work, lack of family support, and lack of knowledge as the most frequent barriers to achieving self-management. 18 While men in our study also identified the latter two as challenges, lack of time at work was not discussed as a barrier; in this sample nearly all of the participants were unemployed. The importance of convenience and ease of access emerged as key factors for participation in a community-based intervention.…”
Section: Discussionmentioning
confidence: 56%
“…24,25 Unden et al (2008) found that men with type 2 diabetes reported fewer diabetes-related worries and better coping abilities than men, while Chlebowy et al (2013) reported men were more likely to use more problem-focused and less emotion-focused methods for diabetes self-management. 18,26 The participants in our study frequently cited low self-esteem, depression, denial, and fear as emotional hurdles. Additionally, some of the greatest needs that emerged from the focus groups included emotional support and support group meetings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Education was provided during the day: comments from participants indicated that they did not want to close their shop or could not find anyone to cover for them; students had classes and others were working. A previous USA study found that men of African American origins [28] were able to take time away from work for GP appointments, normally of shorter duration than an education session, but not for education for self management. We had planned to use two of the Conversation Maps TM over different sessions but this did not occur due to participants' comments that they were not able to return for a second session.…”
Section: Recruitment and Attendancementioning
confidence: 98%
“…African-American women have been found to have greater perceived barriers to self-management than men [9]. However, few studies examine why these barriers exist.…”
Section: Introductionmentioning
confidence: 99%